The Role of Pentahelix Collaboration and Public Perception in Urban and Regional Planning and Sustainable Urban Development in Jakarta - Dananjaya, Ahmad Ghazy (Department of Urban and Regional Planning, Faculty of Engineering, Universitas Tanjungpura, 2025)
Abstract: This study analyzes the effectiveness of urban and regional planning and sustainable urban development in Jakarta, focusing on Pentahelix collaboration and public perception. As a rapidly developing megacity, Jakarta faces complex urbanization challenges, including extreme population density, informal settlements, environmental degradation, and socioeconomic disparities. This research addresses a significant literature gap by integrating multi-stakeholder perspectives from the Pentahelix model